“Honor Your Father and Mother” or “Honor Your Mother and Father?”: A Case Study in Creole Bible Translation - Winedt, Marlon (The Bible translator, 2007)
We recognize also that there are many languages for which gender distinction in grammatical forms is not an issue, as the same form serves for both masculine and feminine. However, this feature of language does not necessarily mean that those language groups do not discriminate on the basis of gender in [the] other areas.